Rating Government Procurement Markets - Tatyana Deryugina; Alminas Zaldokas; Anastassia Fedyk; Yuriy Gorodnichenko; James Hodson; Ilona Sologoub (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We develop a novel, scalable method for assessing the quality of public procurement systems using standard administrative data. Our approach compares the distribution of procurement opportunities to the distribution of contract awards across firms. We first derive a simple theoretical benchmark that relates the expected distribution of contract value winning firms, measured as a Herfindahl-Hirschman index (HHI), to the distribution of auction values, measured as a respective HHI, and the number of winning firms. Significant deviations of winning firms' HHI from this benchmark indicate potential governance failures such as corruption or unchecked collusion. Our method requires no subjective input, is transparent and reproducible, and allows for meaningful comparisons across countries, industry sectors, and over time. We use procurement data from Ukraine and EU member states in 2018-2021 to assess the performance of five large sectors. Results indicate that Ukraine's procurement performance in four of the five sectors is comparable to many other European countries. However, Ukraine's construction sector consistently displays the largest excess concentration among all countries considered, consistent with anecdotal evidence of corruption in this sector. Overall, with minimal data requirements, our method offers a practical tool for cross-sector and cross-country assessment of procurement systems.
Keywords: D73; L10; H11; 330; procurement; corruption; Ukraine; collusion